2018
DOI: 10.1016/j.cgh.2017.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Nonalcoholic Fatty Liver Disease Prevalence, Severity, and Outcomes in the United States: A Systematic Review and Meta-analysis

Abstract: In a systematic review and meta-analysis, we found significant racial and ethnic disparities in NAFLD prevalence and severity in the United States, with the highest burden in Hispanics and lowest burden in Blacks. However, data are discordant on racial or ethnic differences in outcomes of patients with NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
291
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(320 citation statements)
references
References 47 publications
20
291
0
9
Order By: Relevance
“…This is in keeping with a study of adolescents with obesity by Schwimmer et al (34) that demonstrated that those of Black ethnicity had lower prevalence of abnormal ALT levels compared with those of other ethnicities (White and Hispanic), although adolescents of South Asian ethnicity were not included in that study. The same ethnicity-related disparities in NAFLD prevalence in adults has been reported in many studies (35).…”
Section: Discussionsupporting
confidence: 76%
“…This is in keeping with a study of adolescents with obesity by Schwimmer et al (34) that demonstrated that those of Black ethnicity had lower prevalence of abnormal ALT levels compared with those of other ethnicities (White and Hispanic), although adolescents of South Asian ethnicity were not included in that study. The same ethnicity-related disparities in NAFLD prevalence in adults has been reported in many studies (35).…”
Section: Discussionsupporting
confidence: 76%
“…Despite its high prevalence, NAFLD was described by a relatively non‐specific code in ICD‐9‐CM: 571.8 ‘Other Chronic Non‐Alcoholic liver disease’ until October 2015 . Thus, population‐based studies, including ours, rely upon related conditions since approximately 50% of patients with diabetes, obesity and metabolic syndrome also have NAFLD . We were unable to identify and remove treated HBV‐HCC and HCV‐HCC cases.…”
Section: Discussionmentioning
confidence: 96%
“…Prior studies have suggested racial/ethnic group's prevalence differs for NAFLD and those with NAFLD‐related fibrosis . However, population‐based data for Asian Americans have been limited with a most recent study reporting that the prevalence of NAFLD amongst Asian Americans was 18% which is considerably lower than reported for non‐Hispanic Whites at 24% .…”
Section: Introductionmentioning
confidence: 89%